Head as metaphor in Paul - Wolters, A. (Koers, 2011)
Since the 1980s there has been a debate among New Testament scholars about the meaning of the Greek word “kephal?” (“head”) in the Pauline epistles. Some scholars defend the traditional view that it means “leader”, while others argue that it should be understood to mean “source”. One result of this debate is that it is now clear that both the traditional and the new interpretation of kephal? have very little support in general Greek usage before the New Testament. This article seeks to advance the debate by showing that the phenomenon of “semantic borrowing” can explain why the meaning “source” is effectively limited to one passage in Herodotus,and the meaning “leader” is only found in Greek works written by bilingual Jews. The passage in Herodotus probably reflects a semantic loan from Old Persian *sar while various places in the Septuagint, Philo, Josephus and Paul reflect a semantic loan from Hebrew “ro’sh” (or Aramaic “re’sh”). Because the latter semantic loan (“head” meaning “leader”) is embedded in the Greek Bible (both in the Septuagint and Paul),the authority and prestige of the latter can account for the fact that the new meaning of kephal?, though unknown in previous pagan Greek writings, gradually became widespread in postbiblical Greek as Christianity spread.